2019
DOI: 10.1021/acs.chemmater.9b02551
|View full text |Cite
|
Sign up to set email alerts
|

Control of a Dual-Cross-Linked Boron Nitride Framework and the Optimized Design of the Thermal Conductive Network for Its Thermoresponsive Polymeric Composites

Abstract: With the development of polymer-based composite materials technologies and the continuous expansion of its application scale, the research focus has shifted from performance and quality to multifunctionality. Conventional thermally conductive composites are static and passive. Thermoresponsive polymeric composites are dynamic and active; they are able to perceive changes in ambient temperature and exhibit simple and direct responses, which have attracted considerable attention. Herein, thermoresponsive polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(40 citation statements)
references
References 46 publications
(88 reference statements)
1
39
0
Order By: Relevance
“…Therefore, the improvements in thermal conductivity of polymer materials, especially their through-plane thermal conductivity, are highly crucial for their application as thermal interface materials (TIMs) between heaters and heat sinks [5]. To achieve this goal, metallic, ceramic, and carbon-based thermally conductive fillers, such as silver nanoparticles [6,7], boron nitride nanosheets [8][9][10], carbon nanotubes [11], graphite [12,13], and graphene sheets [14][15][16][17], are compounded with polymers. Among these conducting fillers, graphene becomes highly promising because of its exceptionally high in-plane thermal conductivity (~ 5300 W m −1 K −1 ) and mechanical properties [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the improvements in thermal conductivity of polymer materials, especially their through-plane thermal conductivity, are highly crucial for their application as thermal interface materials (TIMs) between heaters and heat sinks [5]. To achieve this goal, metallic, ceramic, and carbon-based thermally conductive fillers, such as silver nanoparticles [6,7], boron nitride nanosheets [8][9][10], carbon nanotubes [11], graphite [12,13], and graphene sheets [14][15][16][17], are compounded with polymers. Among these conducting fillers, graphene becomes highly promising because of its exceptionally high in-plane thermal conductivity (~ 5300 W m −1 K −1 ) and mechanical properties [18].…”
Section: Introductionmentioning
confidence: 99%
“…With continuingly increasing power of electronic devices, the amount of heat generated is sharply increasing. [1][2][3][4][5] Owing to roughness in morphology, just a small fraction of the apparent surface area will have an actual contact when two solid surfaces are joined. [6][7][8][9][10] The rest of the area will be separated by an air-filled gap, and since the thermal conductivity of air (0.026 W/mK) is about four orders of magnitude lower than that of metals, heat transfer across the interface through air is negligible.…”
Section: What Is Thermal Interface Material?mentioning
confidence: 99%
“…Therefore, the thermal problem near the chip is very severe. The total thermal resistance for non-uniform heating can be written as: 15 ψ ja = DF × R jc + ψ cs + ψ sa (2) where ψ ja is the junction to ambient thermal resistance, R jc the junction to case thermal impedance for an uniformly heated die, ψ cs is the case to sink resistance, and ψ sa is the sink to ambient thermal resistance. DF in Eq.…”
Section: Figmentioning
confidence: 99%
“…As shown in Figure a, the XPS spectrum of BNNS had three peaks located at 191.4, 398.0, and 537.0 eV, assigned to B, N, and O, respectively. [ 25 ] For the f‐BNNSs, there was a new peak located at 286.0 eV, which can be assigned to C (Figure 2b). [ 22 ] The curves of f‐BNNS could be fitted into three peaks located at 285.0, 286.1, and 287.8 eV, attributed to the C from CC, CN, and CO groups of the PNIPAM chain, respectively (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with pure f‐BNNS, the peak of MAH‐β‐CD/f‐BNNS solution exhibited a significant shift, which indicated that f‐BNNS had a strong interaction with polymer matrix. [ 26,25,28 ] Scanning electron microscopy (SEM) was used to characterize the microstructures of the hydrogels. As shown in Figure 3b, the pure PNIPAM hydrogel exhibited a uniform pore structure with a size of ≈20 µm.…”
Section: Resultsmentioning
confidence: 99%